Visual analysis of the research hotspots in neoadjuvant therapy for patients with gastric cancer - Chen, Tianxing; Liu, Yating; Gao, Jing; Zhang, Dekui (Frontiers in Gastroenterology, 2023)
Objective This study aimed to analyze the research hotspots and frontiers in the field of neoadjuvant therapy for patients with gastric cancer (GC) using bibliometric and identify its developmental trends. Methods The literature related to neoadjuvant therapy for GC systematically retrieved between 1991 and 2021. Bibliometric methods were used to analysis the research hotspots and trends by CiteSpace and VOS-viewer software. Results The number of studies related to neoadjuvant therapies for GC showed an upward trend. Moreover, the current research directions were mostly focused on the clinical trials and applications of neoadjuvant therapies for GC. The frontier research directions included microsatellite instability, peritoneal metastasis, randomized controlled trials, multicenter studies, and regression analysis. Conclusions The interest and attention of researchers in this field are still growing. In the past five years, the literature related to neoadjuvant therapy and immunotherapy for gastric cancer has exploded. It is still an important period and a key stage for the development of neoadjuvant therapy for gastric cancer.